PROPOSED DIGITAL MARKETING STRATEGY TO CREATING BRAND AWARENESS FOR NEW BRAND ESTABLISHMENT (CASE STUDY : YUGEN) (The Indonesian Journal of Business Administration, 2021)
The Indonesian Creative Economy has good potential with extraordinary economic value, this economic growth is supported by the increasing number of companies from various industrial sectors. This can be seen from the data from the Indonesian Creative Agency (BEKRAF), it is noted that the fashion industry is in the second largest rank of 18.15% after Culinary 41.69% in Indonesia on 2018. Over time, the necessity of fashion is influenced by the large human population in Indonesia. Judging from the high demand for fashion every year in Indonesia, it opens up great opportunities for YUGEN to try to take advantage of opportunities to enter the world of the fashion industry. However, with so many competitors making YUGEN have to find the best strategy to develop in the fashion industry, this study aims to find the right marketing strategy to be implemented in the company to create brand awareness that will increase future sales. By analyzing internal and external factors as the first step in this research, using several methods to analyze internal factors, namely Segmenting, Targeting, Positioning(STP), and Marketing Mix (4P). Meanwhile, the external analysis uses three methods of Consumer analysis, Customer analysis, and Proter's Five Forces. For data collection, YUGEN uses quantitative and qualitative methods by distributing questionnaires which are represented in numerical form (Qualitative), which will then be described using detailed ideas and insights (Qualitative) so that readers can see the meaning of these numbers.Keyword: Fashion Industry, Marketing Content, Digital Marketing, Create BrandAwareness